Scratching the surface of war. Airborne laser scans of the Great War conflict landscape in Flanders (Belgium). (January 2018) - Gheyle, Wouter; Stichelbaut, Birger; Saey, Timothy; Note, Nicolas; Van den Berghe, Hanne; Van Eetvelde, Veerle; Van Meirvenne, Marc; Bourgeois, Jean
Abstract: In light of the growing interest in the Great War – stimulated by the ongoing centennial commemorations – the conflict landscape in Belgium and France is currently the subject of scientific research projects, archaeological excavations, heritage-related initiatives and exhibitions. However, the extent of the archaeological heritage and surface remains of the Great War remain underestimated. Current heritage management and the proposal for a UNESCO nomination focus on the architectural heritage, commemorative monuments and military cemeteries, thereby overlooking the opportunities to acknowledge the conflict landscape in its totality. This paper explores the application of high-resolution Lidar data (DTM-Flanders II 2013–2015) to investigate a layer of war heritage which, until now, has remained invisible, and reveals a wide range of previously unknown archaeological sites related to the Great War. Traces of the war can be found all over the former front zones and hinterland, ranging from remnants of the heavily shelled and devastated war landscapes to more specific archaeo-geomorphological features of trenches, dugouts and other military infrastructure. Both the nature and the scale of the new information support and further expand the concept of the landscape as the last witness of the war. Graphical abstract: Highlights: Lidar visualisations reveal a wide range of previously unknown Great War sites. Over 12% of the study area covered with surface traces of the Great War. 3D information enhances our knowledge of the typology of war features. Implications for research, heritage management and development of conflict landscapes.